Tác động của trách nhiệm xã hội doanh nghiệp về môi trường đến hành vi xanh của nhân viên – Một nghiên cứu trong lĩnh vực khách sạn tại Việt Nam - Trịnh Thị, Hà; Nguyễn Thị Phương, Thảo; Bạch Văn, Lượng; Nguyễn Văn, Anh (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study aims to explore the relationship between environmental corporate social responsibility (ECSR) and employee green behavior in the hotel sector, and test the mediating role of well-being factors and organizational identification in the above relationship. As one of the very few studies using social information processing theory in the hotel industry and using quantitative research methods, the research results have shown that employees green behavior is significantly positively influenced by the company's environmental corporate social responsibility, employee well-being, and organizational identification. Employee well-being and organizational identification play a partial mediating role in the relationship between ECSR and employee green behavior. The research results reinforce the important role of ECSR activities in the green behavior of employees in the hotel sector.
Keywords: Corporate social responsibility; Employee green behavior; Organizational identification; Employee well-being